Analysis Of The Implementation Of Law N0. 24 Year 2011 Concerning BPJS Employment In Protecting Workers In Indonesia - Dimas Putra Prihananto; Fadlan Fadlan (International Journal of Law, Crime and Justice, 2024)
This research aims to analyze the extent of the implementation of Law No. 24/2011 concerning BPJS Employment in providing protection for workers in Indonesia. The focus of this research is to assess whether the implementation of the policy is in accordance with the expected objectives, as well as to identify factors that affect its success or failure. To identify various obstacles and barriers faced in the implementation of BPJS Ketenagakerjaan, both from the side of the workforce, the employer, and the government. This research uses a qualitative descriptive method. The descriptive qualitative method was chosen because it aims to describe and analyze the implementation of Law No. 24/2011 in the implementation of the Employment BPJS program and to identify various obstacles, barriers, and their effectiveness in protecting the workforce. Through this approach, the research focuses on in-depth exploration of existing phenomena, utilizing qualitative primary and secondary data. The results of the study explain that BPJS Ketenagakerjaan, which is regulated in Law No. 24 of 2011, plays an important role in providing social protection for workers in Indonesia through various programs such as Old Age Security (JHT), Pension Security (JP), Work Accident Security (JKK), and Death Security (JKM). However, the implementation of BPJS Ketenagakerjaan still faces obstacles, such as low participation of informal sector workers, lack of understanding of BPJS benefits, and complicated claim procedures. To increase its effectiveness, more intensive efforts are needed in socialization to workers and job information providers, as well as simplifying administrative procedures. In addition, the government and BPJS must utilize technology to facilitate access and claim submission. Strict law enforcement against companies that do not comply with their obligations will guarantee compliance and ensure more equitable social protection for all workers in Indonesia.